Tracking architectural defects in residential project in Malaysia / Najihah Rahimin ... [et al.] - Rahimin, Najihah; Mohd Isa, Haryati; Mohd, Thuraiya; Ahmad, Nur Azfahani (Universiti Teknologi MARA, Perak, 2024)
Building defects are always a key concern in the construction industry. Defects represent not only a loss to the project but also hamper the smooth operation of a building. Recognising the need to resolve these continuing problems, research was mooted to track the study of defects that occurred during the Defects Liability Period for residential projects in Malaysia. This paper presents part of the research that investigates what can be learned from the analysis of architectural defects in this project. Two research objectives were developed: (1) to investigate types of architectural defects that occurred, (2) to analyse the causes of the defects, and (3) to categorise the causes of the defects. A mixed methods approach is adopted. Data for the quantitative element of the research was drawn from the project's defect records. They were sorted, grouped and transferred into the SPSS software for analysis using frequency analysis. The findings suggest defects can be effectively traced and categorised with a proper methodology in place. This can provide useful insights into their root cause and how it can be avoided in future projects.